Comparison of Clinicopathological Characteristics Between the Anterior and Posterior Type of Squamous Cell Carcinoma of the Floor of the Mouth: The Anterior Type Is a Risk Factor for Multiple Primary Cancer - Oikawa, Yu; Tanaka, Kae; Ohsako, Toshimitsu; Kugimoto, Takuma; Kuroshima, Takeshi; Hirai, Hideaki; Tomioka, Hirofumi; Shimamoto, Hiroaki; Michi, Yasuyuki; Sakamoto, Kei; Ikeda, Tohru; Harada, Hiroyuki (Frontiers in Oncology, 2021)
Background Floor of the mouth (FOM) squamous cell carcinoma (SCC) accounts for approximately 10% of all oral SCCs. FOM SCC can be classified into the anterior and posterior types according to their site of origin, but few studies have compared these types. This study sought to clarify differences in clinicopathological characteristics between these two types. Methods A total of 1,220 patients with oral SCC were treated at our department from January 2001 to December 2015. Among these patients, 62 had FOM SCC. The FOM SCCs were classified into two groups: the anterior type and the posterior type. The anterior and posterior types were defined by the boundary connecting the spaces between the canine and the first premolar bilaterally. We retrospectively compared the sex, age, smoking and drinking history, clinical stage, treatment, histopathological diagnosis, multiple primary cancers, and outcomes of the two groups. Results Among the 62 patients, 32 had the anterior type, while 30 had the posterior type. The anterior type was found more significantly in men (p = 0.01) and individuals with a smoking history than the posterior type (p = 0.04). pN2–3 cervical lymph node metastasis was significantly more common in the anterior type than in the posterior type (p = 0.01). The median depth of invasion in the anterior type was 4 mm. Multivariate analysis showed that the anterior type was an independent risk factor for multiple primary cancer development in FOM SCC (p = 0.02). The cumulative 10-year disease-specific survival rates of the anterior and posterior types were 92.8 and 95.0%, respectively, while the overall survival rates were 65.4 and 95.0%, respectively. In the anterior type FOM SCC, a lower overall survival rate was associated with multiple primary cancers and smoking-related diseases. Conclusion Smoking cessation and adequate systemic screening for multiple primary cancers are needed to improve the prognosis of FOM SCC, particularly the anterior type.